The greater east Asia co-prosperity sphere : when total empire met total war - Yellen, Jeremy A., 1977- (Studies of the Weatherhead East Asian Institute, Columbia University., 2019)
"This book explores the Greater East Asia Co-Prosperity Sphere, Japan's ambitious wartime attempt to create a new order in East and Southeast Asia"--